Cultivation of Seaweed Kappaphycus alvarezii with Various Substrates Different on Laboratory Scale - Jum'at, Muhammad; Cokrowati, Nunik; Lumbessy, Salnida Yuniarti (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
Kappaphycus alvarezii is an important red algae and can be used as one of the primary raw materials in fisheries. It is widely cultivated because of its relatively cheap production technology, and post-harvest handling is simple and easy. This algae has excellent economic value for carrageenan producers. Carrageenan is used as a food ingredient, cosmetics, and medicine. The success of cultivating K. alvarezii seaweed can be achieved if a suitable environment for its growth supports it. One of the environmental aspects that influence the growth of K. alvarezii seaweed is the bottom substrate of the waters. This research aims to analyze the best substrate for cultivating green K.alvarezii seaweed on a laboratory scale. This research used an experimental method with a Completely Randomized Design (CRD) consisting of 4 treatments and three repetitions, resulting in 12 experimental units. The treatments tested were different substrates: a coral substrate, a sand substrate, a volcanic rock substrate, and a coral sand substrate. The results of this study showed that the average survival rate in various substrate treatments ranged from 7.16% to 39%, final weight ranged from 1.43 g to 7.8 g, specific loss rate ranged from -3.157%/day to -5.124%/day, carrageenan yield ranged from 6.8% to 18.4%, and thallus tissue showed that all treatments still showed the presence of cortex and medullary tissue with varying shapes and structures